DIRECTIONS OF COST OPTIMIZATION IN THE SYSTEM OF IMPROVING THE QUALITY OF LOGISTIC ACTIVITY OF THE ENTERPRISE - SAVIN, STANISLAV; DZHERELIUK, YULIIA; VOSKRESENSKA, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article systematizes the directions of cost optimization in the system of improving the quality of logistics activities of the enterprise. The essence of the concept, the significance of logistics, as the basis of effective development of enterprises is сonsidered. Views on cost management by different scholars are analyzed. It is generalized that the main goal of logistics cost management is to find the most efficient way to use the available limited logistics resources. Optimizing the costs of the enterprise in a changing environment and increasing market competition is one of the most important management tasks of each business entity. The logistics activities of the company play a key role in promoting products from producer to consumer of goods and services. Effective logistics processes at the enterprise and elimination of excessive logistics costs, therefore, saves total costs, reduces the cost of goods and services, improves the quality of logistics processes and allows more systematic assessment and forecasting of financial results. It is determined that the improvement of the system of information support of management processes is one of the conditions for improving the quality of logistics activities of the enterprise. It is argued that the components of the information strategy to minimize logistics costs should harmoniously combine the main provisions of the strategy of information perception, strategy of analysis and interpretation of information, information dissemination strategy, information security strategy. Options for reducing the costs of the enterprise depending on the form of its cooperation with small and large enterprises are summarized. It is determined that one of the conditions for reducing the costs of the enterprise is to assess the optimal ratio of production, costs and profits.